Misión de la educación superior en una frontera de épocas - Ángel Ruiz-Zúñiga (Universidad Nacional, Costa Rica, 2004)
Analysis of the main trends found in the historical scenario we live in: the Post Cold War period, globalization, disruption of Modernity, transition and limits of historical ages, and above all, modern knowledge as the builder of a new era. The main characteristics that define higher education are reviewed within this context; these traits are: expansion, diversification, its new relationship with the social context, transdiscipline, permanent education, radical internationalization and globalization, as well as quality and social adequacy as a basis in university activities. This is part of the redefinition of the main variables that characterize university activities.